Association of Behçet’s disease with the risk of metabolic syndrome and its components: a systematic review and meta-analysis - Chen, Tingqiao; Shao, Xinyi; Li, Hao; Chen, Yangmei; Liu, Lin; Zhong, Judan; Chen, Jin (Clinical and experimental medicine, 2023)
The present meta-analysis aimed to elucidate the association of Behçet’s disease (BD) with the risk of metabolic syndrome (MetS) and its components. Observational cohort studies were searched from the Embase, Web of Science, Medline, and Cochrane Library databases. The primary outcome was the association of BD with the risk of MetS and its relevant components. Effect estimates with odds ratios (ORs) were pooled using either the random-effects or fixed-effects models, according to heterogeneity. Leave-one-out sensitivity analyses were used to determine the stability of the results. Twenty-three studies, comprising 42,834 patients with BD, were included. Overall, a significant association between BD and the risk of MetS was found (pooled OR 2.26; 95% confidence interval [CI] 1.61–3.17; P < 0.0001). Among the components of MetS, significant associations were found between BD and diabetes mellitus (OR 1.21; 95% CI 1.10–1.33; P < 0.0001), BD and hypertension (OR 1.39; 95% CI 1.13–1.70; P = 0.002), and BD and dyslipidemia (OR 1.21; 95% CI 1.01–1.45; P = 0.04). Our study indicated an association between BD and the risk of MetS and some of its components (diabetes mellitus, hypertension, and dyslipidemia). Physician should consider these associations so that specific treatments are available for patients with comorbidities. Moreover, patients with BD should regularly monitor their blood pressure, fasting plasma glucose, and blood lipid levels.